Green Synthesis of Silver and Copper Nanoparticles Using Ascorbic Acid and Chitosan for Antimicrobial Application - Norashikin, Mat Zain; Stapley, A. G. F.; Shama, G. (Elsevier Ltd, 2014)
Silver and copper nanoparticles were produced by chemical reduction of their respective nitrates by ascorbic acid in the presence of chitosan using microwave heating. Particle size was shown to increase by increasing the concentration of nitrate and reducing the chitosan concentration. Surface zeta potentials were positive for all nanoparticles produced and these varied from 27.8 to 33.8 mV.Antibacterial activities of Ag, Cu, mixtures of Ag and Cu, and Ag/Cu bimetallic nanoparticles were tested using Bacillus subtilis and Escherichia coli. Of the two, B. subtilis proved more susceptible under all conditions investigated. Silver nanoparticles displayed higher activity than copper nanoparticles and mixtures of nanoparticles of the same mean particle size. However when compared on an equal concentration basis Cu nanoparticles proved more lethal to the bacteria due to a higher surface area. The highest antibacterial activity was obtained with bimetallic Ag/Cu nanoparticles with minimum inhibitory concentrations (MIC) of 0.054 and 0.076 mg/L against B. subtilis and E. coli, respectively.